Κινητική μελέτη εκχύλισης χρωστικών και φαινολικών ενώσεων κατά τη παλαίωση αποστάγματος ζιβανίας με δρύινα τεμαχίδια ξύλου - Μουσική, Χριστιάνα (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The present study titled ¨Development study of pigments and phenolic compounds during aging of zivania distillate with oak wood particles ¨ was carried out in the framework of dissertation work. The main objective was the development of an innovative product that results from the aging of zivania, “Black” and “Sultanina” variety and its study regarding, the kinetics of extraction of pigments and phenolic compounds. Aging was carried out with medium or heavily roasted wood particles, from oak, for a period of thirty days. Another objective was to study the effect of the concentration (2, 4% w/v) of the particles and the degree of roasting of the particles on the rate of transfer of the components. In addition, the volatile compounds of the aged distillates were determined, by using GC-FID, in order to determine whether the spirits produced meet Legislative requirements and whether the product resulting from aging of zivania can be actually called zivania. At the end of the study, the great effect of the aging process on the color of the distillate and the concentration of polyphenols and tannins was obvious. The concentration of polyphenols, tannins and color increased rapidly and exponentially especially during the first days of the aging process. With regard to the changing factors during the aging process, it was of particular importance the concentration of wood particles, with higher concentrations lead to increasing percentages of polyphenols, tannins and color.
Keywords: Aging of zivania; Oak chips; Pigments; Phenolic substances; Volatile components; Παλαίωση ζιβανίας; Τεμαχίδια ξύλου δρυός; Χρωστικές; Φαινολικές ουσίες; Πτητικά συστατικά